First zoeal stage morphology of Alpheus carlae and A. intrinsecus (Decapoda, Caridea, Alpheidae) obtained in the laboratory - Pantaleaõ, Joaõ Alberto Farinelli [UNESP]; Pescinelli, Régis Augusto [UNESP]; Costa, Rogério Caetano [UNESP]; Cuesta, Jose A.; Mantelatto, Fernando Luis (Cambridge University Press (CUP), 2020)
The first zoeal stages of the snapping shrimps Alpheus carlae and A. intrinsecus from Brazil were obtained from laboratory-hatched specimens and a detailed morphological description is provided. The morphological characteristics of both species are compared with available descriptions of other Alpheus species with a known first zoeal stage. Remarks from a semi-quantitative comparison of species belonging to A. armillatus species complex (A. carlae and A. brasileiro) and a comparison between larvae of A. intrinsecus from two localities in Brazil are presented. It was possible to distinguish first zoea of both species from the other congeners based on morphology. No intraspecific variability was detected between A. intrinsecus larvae obtained from two locations. Some structures showed differences between species of the A. armillatus complex. However, generalizations and conclusions based on larval morphology for taxonomic rearrangements at this point need to be made with caution and accuracy, since data of a sufficient number of species are not yet available for comparison.
Keywords: Decapoda; larval development; larval morphology; snapping shrimp